Perkembangan Pengobatan Topikal Untuk Dermatitis Seboroik Wajah - Azaria Ramadhani Zulkifli; Rina Gustia; Taufik Ashal (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background: Seborrheic dermatitis is a chronic and recurring skin disorder with clinical manifestations as erythematous macules or plaques with a scale associated with pruritus. The most common predilection is the face area. Treatments for seborrheic dermatitis should address the normalization process of skin function and structure, not only relieving the symptoms and clinical symptoms of the disease. Thus, leading to long-term remission. Objective: The narrative review was conducted by reviewing the articles that discussed about the treatment effectiveness on facial seborrheic dermatitis. Methods: Articles search was carried out through databases such as Pubmed and Google Scholar with determined keywords and selected based on inclusion and exclusion criteria. Results: In total, six articles were reviewed with 184 cases of facial dermatitis seborrheic. All studies showed significant improvement. This review included additional literatures to support the results of the main literatures. Conclusion: The treatments commonly used for seborrheic dermatitis these days are pharmacological treatments in the form of topical and systemic drugs as well as non-pharmacological treatments. Topical drugs were able to repair the clinical manifestation on mild to moderate seborrheic dermatitis whereas systemic drugs were indicated for cases with wide lesions and more severe condition. Non-pharmacological treatment can be used as an adjuvant to accelerate the clinical condition.